Classifying the productivity of drained peatland forests for precision management - Salmivaara, Aura; Tuominen, Sakari; Laiho, Raija; Ahtikoski, Anssi; Haikarainen, Soili; Lehtonen, Aleksi; Mäkipää, Raisa (Springer Nature, 2026)
Utilizing advancements in peatland mapping, spatial analysis of drainage intensity, and automated segmentation of forest resource data, we produced an openly available dataset to classify drained peatland forests in Finland based on productivity. Five classes were separated: unproductive, low-productive, medium-productive, and productive, the latest including a separate class for young stands. Productivity was assessed through tree stand volume development, using consecutive Multi-Source National Forest Inventory (MSNFI) data from 2000 to 2021. Our results show that approximately 83% of forestry-drained peatlands were productive or medium-productive. The identified poorly productive areas (unproductive i.e. volume < 30 m3ha−1 excluding young stands, and low-productive i.e. volume < 45 m3ha−1) covered an area of 782 000 ha (17% of all forestry-drained peatlands). Earlier classification of economic feasibility for timber production, based on temperature sum and site fertility class, yielded larger poorly productive areas, but increasing temperature sums seems to decrease their area. Besides temperature sum, drainage intensity and fertility class explained the lowest and highest classes of productivity. Poorly productive drained peatland forests were primarily located in the northernmost regions. The produced dataset includes stand boundaries, most recent stand information from MSNFI, stand productivity classification (1–5), ditch density and spacing, and site fertility class, and supports targeted decision-making for the management of drained peatland forests, greenhouse gas emission reduction, the restoration law, and the freshwater directive of the European Union.
Keywords: peatland management; boreal; climate change; ditch density; spatial dataset; restoration